2003
DOI: 10.1002/anie.200351267
|View full text |Cite
|
Sign up to set email alerts
|

InBr3‐Catalyzed Cyclization of Glycals with Aryl Amines

Abstract: Dedicated to Professor Goverdhan Mehta on the occasion of his 60th birthdayGlycals are ambident electrophiles capable of reacting with various nucleophiles such as alcohols, malonates, and silyl nucleophiles under the influence of acid catalysts or oxidants to produce 2,3-unsaturated glycosides. [1,2] In recent times, indium halides have emerged as versatile Lewis acid catalysts imparting high regio-, chemo-, and diastereoselectivity to a variety of organic transformations.[3] Compared to conventional Lewis ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
41
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 14 publications
6
41
1
Order By: Relevance
“…But instead of desired products we ended up with one interesting unusual adduct 47. While this work was in progress Jadav et al 52 reported results on InBr 3 catalyzed reactions at room temperature, which supports our observation. They used CH 2 Cl 2 and the same kind of aniline donors, and obtained the same type of cyclic compounds (Scheme 35).…”
Section: Scheme 31supporting
confidence: 92%
“…But instead of desired products we ended up with one interesting unusual adduct 47. While this work was in progress Jadav et al 52 reported results on InBr 3 catalyzed reactions at room temperature, which supports our observation. They used CH 2 Cl 2 and the same kind of aniline donors, and obtained the same type of cyclic compounds (Scheme 35).…”
Section: Scheme 31supporting
confidence: 92%
“…10 Although the reaction also proceeded with InCl 3 , InBr 3 was found to be superior in terms of yield and reaction rate. This reaction can also be performed with stoichiometric amounts of TMSOTf.…”
Section: Abstractsmentioning
confidence: 97%
“…Most of the methods employed the hetero Diels-Alder method using different Lewis acids such as BF 3 ·OEt 2 [9], ZnCl 2 [10], BiCl 3 [11], and InCl 3 [12,13] and Brönsted acids such as HBF 4 , CF 3 COOH, TsOH [14], and also mineral acids [15] to produce 2,3-tetrahydroquinolinated pyranose derivatives. Recently, Yadav et al reported the synthesis of 2,4-tetrahydroquinolinated pyranose derivatives using InBr 3 , Bi(OTf) 3 , and CeCl 3 /NaI [16][17][18]. Many of these methods having one or more disadvantages such as high acidity, long-reaction times, high reaction temperatures, use of stoichiometric amounts of reagents, difficulty in preparation of the catalyst, and most of these methods were conducted under moisture-free conditions.…”
Section: Introductionmentioning
confidence: 98%